Implementation of the Compulsory Nine-Year Basic Education Program: Opportunities and Constraints at Household and Community Level - Titik Handayani; Soewartoyo Soewartoyo; Makmuri Sukarno (Journal of Indonesian Social Sciences and Humanities, 2009)
-